2018
DOI: 10.1002/slct.201802068
|View full text |Cite
|
Sign up to set email alerts
|

A3B Porphyrins Bearing Thienyl/Pyridyl Moieties Obtained via Scrambling: Characterization, DNA interaction and Anticancer Studies

Abstract: Condensation of 3‐pyridine carboxaldehyde with 2/3‐thienyl dipyrromethanes in presence of acid catalyst gives 5‐(3′‐pyridyl)‐10,15,20‐tri(2/3‐thienyl)porphyrins (S1a and S2a) due to scrambling along with the expected trans‐porphyrins. The corresponding copper(II) and zinc(II) porphyrins were also synthesized. Moreover, to study their biological properties their cationic derivatives were obtained. All the complexes were characterized by UV‐Vis, fluorescence, NMR spectroscopy, mass spectrometry and cyclic voltam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…In conclusion, a new type of hydrophilic cationic porphyrin is introduced. Unlike pyridyl groups, thienyls are not readily alkylated. , In this report, a simple solvent driven process has afforded the desired alkylated thiophenium cation. A clear indication of stronger photocytotoxicity, toward A549 lung cancer cell lines, is apparent in the presence of a higher number of the cationic meso -4-methylthiophenium groups in the reported porphyrins.…”
mentioning
confidence: 99%
“…In conclusion, a new type of hydrophilic cationic porphyrin is introduced. Unlike pyridyl groups, thienyls are not readily alkylated. , In this report, a simple solvent driven process has afforded the desired alkylated thiophenium cation. A clear indication of stronger photocytotoxicity, toward A549 lung cancer cell lines, is apparent in the presence of a higher number of the cationic meso -4-methylthiophenium groups in the reported porphyrins.…”
mentioning
confidence: 99%
“…The binding energy of all the porphyrins understudy is around À 10 kcal/mol, and the values are comparable with our previously reported A 3 B porphyrins . [8] The minor groove binding mode is preferred over intercalative binding due to their increased specificity, lower toxicity, and most importantly, they are non-mutagenic. [23,24] Few commercially available compounds like DB75, pentamidine, and berenil have been found to have biological activity against parasitic organisms previously due to their minor groove binding mode.…”
Section: Docking Studiesmentioning
confidence: 99%
“…Cationic porphyrins are considered as the hosts for molecular recognition and therapeutic agents, and the alkylation of the pyridyl nitrogen of meso‐(pyridyl)‐porphyrins is the accepted synthetic strategy to prepare cationic porphyrins. Earlier reports [8,9] reveals that the porphyrins bearing 3‐/4‐pyridinium and thienyl derivatives were found to be excellent groove binders and exhibit a better DNA binding ability than meso‐ aryl porphyrins.…”
Section: Introductionmentioning
confidence: 99%